The effect of flipped-jigsaw learning models on ethical decision-making - Ziyai, Nasibe Yağmur (Nursing ethics, 2024)
BackgroundEthical decision-making education in nursing can be taught effectively by combining different teaching models that support the visualisation of taught concepts and integrating theory into practice.ObjectivesThe study aims to examine the effect of flipped and jigsaw learning models on ethical decision-making and ethical sensitivity in nursing.Research designWe used a nested mixed design. A pretest-posttest single-group quasi-experimental design was used in the quantitative part, and a case study method was used in the qualitative part.Participants and research contextThis study was conducted in fall semester with second-year nursing students who studied an ethics course for the first time, using two different collaborative learning models. In the quantitative part, ethical dilemma and ethical sensitivity scales were made as pre-test with 117 and post-test with 128 students. In the qualitative part, a semi-structured three focus group interviews was conducted with 16 students.Ethical considerationsAfter obtaining the approval of the University’s ethics committee, the study was carried out after obtaining participants’ informed written and verbal consent.FindingsStudents’ perspectives changed positively after training. This was related to six cases in section A of the Ethical Dilemma Scale. In part B, Practical Consideration (PC) and Principled Thinking (PT) mean scores were similar, showing no significant difference. For Familiarity in section C, it was determined that 68.4% of students in the pre-test and 77.3% in the post-test were familiar with similar dilemmas. The ethical sensitivity scale’s total scores were in a similar range. In the qualitative stage, ethical decision-making, ethical sensitivity, ethical dilemma and the improvement process were obtained as a theme.ConclusionsThere was an increase in the level of ethical sensitivity and familiarity with ethical dilemmas of nursing students after education. Flipped and jigsaw learning models can be used for nursing ethics courses.